Metodologia para avaliação de City Building Games (CBG) no contexto da mobilidade urbana - Lima, Bruno Joaquim (Universidade Federal de São Carlos, 2021)
This dissertation seeks to propose a methodology for evaluating CBGs (City Building Games) that can help in the planning processes of urban mobility in Brazilian municipalities, from the perspective of National Urban Mobility Policy (PNMU). The criteria evaluated in the methodology are defined, based on Urban Mobility Plans (PMU) and Transit Oriented Development. Two of the main simulators, SC4 (SimCity 4) and C:S (Cities: Skylines), are evaluated based on the simulation of a region in the city of Araraquara. In this way, it is possible to compare the results and assess the strengths and weaknesses. The methodology allowed us to analyze the CBGs from the perspective of urban mobility, showing the various possibilities for building and evaluating scenarios and allowing the understanding of the impacts over time of a given set of actions. However, the games focus essentially on motorized vehicles (private or collective), leaving the means of active mobility as secondary and not even addressing the issue of universal accessibility for people with disabilities (important issues of PMU). Another important point to highlight is the purely economic view of the city in the context of these games, making it necessary to reflect on how the proposed interventions will affect the social and political dimensions of the affected community.
Methodology for evaluating City Building Games (CBG) in the context of urban mobility
Keywords: Simulação; Mobilidade; Planejamento; Engenharia urbana; Simulation; City Building Game; Mobility; Planning; Urban engineering; ENGENHARIAS